2008
DOI: 10.1128/aem.01973-07
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shadowing on Survival of Bacteria under Conditions Simulating the Martian Atmosphere and UV Radiation

Abstract: Spacecraft-associated spores and four non-spore-forming bacterial isolates were prepared in Atacama Desert soil suspensions and tested both in solution and in a desiccated state to elucidate the shadowing effect of soil particulates on bacterial survival under simulated Martian atmospheric and UV irradiation conditions. All non-spore-forming cells that were prepared in nutrient-depleted, 0.2-m-filtered desert soil (DSE) microcosms and desiccated for 75 days on aluminum died, whereas cells prepared similarly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 41 publications
9
83
0
Order By: Relevance
“…The current study provides evidence that Escherichia coli, a potential spacecraft contaminant (44,53), may survive but not grow on the surface of Mars. Results suggest that desiccation, UV irradiation, high salinity, and low pressure (in decreasing order of importance) were factors in reducing the number of viable E. coli cells over the course of the 7-day Mars simulations, consistent with related studies on microbial survival under Mars conditions (37,39,47,49,51,52).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The current study provides evidence that Escherichia coli, a potential spacecraft contaminant (44,53), may survive but not grow on the surface of Mars. Results suggest that desiccation, UV irradiation, high salinity, and low pressure (in decreasing order of importance) were factors in reducing the number of viable E. coli cells over the course of the 7-day Mars simulations, consistent with related studies on microbial survival under Mars conditions (37,39,47,49,51,52).…”
Section: Discussionsupporting
confidence: 85%
“…Dispersal mechanisms of viable microbes away from landed or crashed spacecraft on Mars have not been adequately studied and remain significant black boxes in any Mars microbial survival and proliferation model. Long-term survival on Mars is unlikely if microbes are directly exposed to solar UV irradiation (11,37,47,49,50) but likely if the microbes are protected from UV irradiation by thin dust layers or embedded within UV-protected niches in spacecraft (33,39,47). In contrast, the greatest unknown in any Mars microbial survival and proliferation model is whether terrestrial microorganisms found on spacecraft are capable of growth and replication under Mars conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UVR-resistant microorganisms have shown tremendous stable biotechnological implications [2,3,29,30]. The short exposure of UV is generally known for random mutagenesis, however microbial reversion may produce unstable mutants with commercially viability.…”
Section: Occurrence Of Microorganisms At Higher Altitudes and Uvrmentioning
confidence: 99%
“…UV-C-radiationresistant Arthrobacter sp. and Bacillus pumilus have been isolated from the Atacama Desert, able to withstand 1000 J/m 2 UV-C radiation [30]. Microorganism Brevundimonas sp.…”
Section: Tolerance and Survivability Of Uvrresistant Extremophilesmentioning
confidence: 99%